2017
DOI: 10.3390/s17122830
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Water Content in Rapeseed Leaves Using Terahertz Spectroscopy

Abstract: The terahertz (THz) spectra of rapeseed leaves with different water content (WC) were investigated. The transmission and absorption spectra in the range of 0.3–2 THz were measured by using THz time-domain spectroscopy. The mean transmittance and absorption coefficients were applied to analyze the change regulation of WC. In addition, the Savitzky-Golay method was performed to preprocess the spectra. Then, the partial least squares (PLS), kernel PLS (KPLS), and Boosting-PLS were conducted to establish models fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…As an advanced technology, terahertz (THz) has received more and more attention in the field of biological sciences [17][18][19]. It has unique absorption characteristics for heterogeneous and biological macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…As an advanced technology, terahertz (THz) has received more and more attention in the field of biological sciences [17][18][19]. It has unique absorption characteristics for heterogeneous and biological macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…This clearly indicated that Weight (g) the moisture in leaves evaporated more rapidly on the day 1 and 2 compared to day 3 and 4, thereby creating more air cavities in the leaves. To assess the variation of leaf WC during the leaf's water evaporation process, the measurements were translated into WC using [17,32],…”
Section: Estimating Leaf Water Contentmentioning
confidence: 99%
“…Over the years, significant amount of contributions have been made [9][10][11][12][13], that address estimating the leaf's WC. There are techniques that offer high reliability yet they are inappropriate for long-term studies of the same plant leaves because of validity of measurements cannot be guaranteed [11,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…THz applications include security screening (García‐rial et al., ; Kaltenecker et al., ; (Liu, Zhong, Karpowicz, Chen, & Zhang, ), astronomical studies (Leisawitz et al., ), communication (Akyildiz, Miquel, & Han, ; Ergün & Sönmez, , nondestructive testing (Probst, Scheller, & Koch, ; Rutz, Koch, Khare, & Moneke, ), medical imaging (Bowman et al., ; Chavez, Bowman, Wu, Bailey, & El‐Shenawee, ; Dougherty et al., ; Fitzgerald et al., ; Sun et al., ; Truong, Fitzgerald, Fan, & Wallace, ), imaging of dental caries (Karagoz, Altan, & Kamburoglu, ; Ripoche, Reynard, Narcisse, & Roberts, ), pharmaceuticals (Markl, Dong, Li, & Zeitler, ; Pei et al., ; Sibik & Zeitler, ; Warnecke et al., , agricultural products (Liu et al., ; Liu, Liu, Hu, Yang, & Zheng, ; Luo, Zhu, Xu, & Cui, ; Nie, Qu, Lin, Dong, & He, ; Ogawa et al., ; Qin, Li, Chen, & Chen, ), food inspection and quality control (Ge, Jiang, Lian, & Zhang, ; Huang et al., , Shin, Choi, & Ok, ; Ok, Park, Kim, Chun, & Choi, ; Ok, Park, Lim, Jang, & Choi, ; Wang, Sun, & Pu, ; Yan, Liu, Qu, & Liu, ), environmental monitoring (Bigourd et al., ), and biosensing and label‐free monitoring of various biological processes (Yang et al., ). Full body THz scanners are installed in many airport checkpoints for detection of concealed objects and explosives.…”
Section: Introductionmentioning
confidence: 99%
“…. Narcisse, & Roberts, 2018), pharmaceuticals (Markl, Dong, Li, & Zeitler, 2018;Pei et al, 2018;Sibik & Zeitler, 2015;Warnecke et al, 2019, agricultural products (Liu et al, 2018Liu, Liu, Hu, Yang, & Zheng, 2016;Luo, Zhu, Xu, & Cui, 2019;Nie, Qu, Lin, Dong, & He, 2017;Ogawa et al, 2006;, food inspection and quality control Huang et al, 2015, Shin, Choi, & Ok, 2018Ok, Park, Kim, Chun, & Choi, 2014;Ok, Park, Lim, Jang, & Choi, 2018;Wang, Sun, & Pu, 2017;Yan, Liu, Qu, & Liu, 2018), environmental monitoring (Bigourd et al, 2006), and biosensing and label-free monitoring of various biological processes . Full body THz scanners are installed in many airport checkpoints for detection of concealed objects and explosives.…”
Section: Introductionmentioning
confidence: 99%